Capacitación laboral y su relación con la gestión administrativa en el personal administrativo de la Corte de Justicia de Loreto año 2024 - Quijano Tafur, Gina Yajaida (2025)
Despite the efforts made in various contexts by governments, companies and programs to promote job and professional training, significant gaps persist in access, quality and alignment of these initiatives with the real needs of the labor market and organizations, which negatively impacts productivity, administrative efficiency and public perception of institutions, the purpose of this study is to identify how job training and administrative management are related in the administrative staff of the Loreto Court of Justice in 2024, from a quantitative approach with an observational nature and a non-experimental design at a correlational level, considering as the study population the collaborators of the Loreto Court of Justice, which amount to 127 people, The results showed that there is a positive and significant relationship between job training and administrative management, with a moderate Spearman correlation (ρ = 0.486; p = 0.000). Specifically, low to moderate positive relationships were found between job training and the dimensions of administrative planning (ρ = 0.374), administrative organization (ρ = 0.393), administrative direction (ρ = 0.472), and administrative control (ρ = 0.467), all with statistical significance. The descriptive analysis showed a high level of staff appreciation for job training, although needs were identified to strengthen technical skills in computer systems and improve interdepartmental supervision and communication mechanisms. The overall conclusion is that strengthening job training programs has a positive impact on administrative performance, consolidating more efficient management processes. It is recommended to implement ongoing training strategies, customized professional development plans, and actions to optimize organizational coordination.